A narrow-band and ultra-low-power 433 MHz wake-up receiver. (November 2019) - Koeble, S; Heller, S; Woias, P
Abstract: For the design of wireless sensor nodes (WSNs) the inclusion of a wake-up receiver becomes interesting as soon as an asynchronous bidirectional communication between the WSN and its host is mandatory, to e.g. reprogram the WSN or to trigger the delivery of data. For these purposes the use of the WSNs standard RF interface is not suitable in most cases, as the high power consumption of the same may drain the WSNs battery or overload the capabilities of an integrated energy harvesting module. To solve this principal conflict between flexibility and power consumption, we present the design and characterization of an ultra-low-power wake-up receiver. The concept is based on an optimized modulation/demodulation concept, to achieve a high RF sensitivity and narrow-band operation at the same time. The final device works in the license-free 433 MHz frequency band, with a high RF sensitivity of -63.4 dBm, an ultra-low power consumption of 8.7 µW, and with a low supply voltage of 2 V only.